Absence of nephroprotective effect: evaluation of an aqueous extract of Clinopodium vimineum (L.) Kuntze (Lamiaceae) using a renal failure model with female Wistar rats - Morales Torres, Katherine (2022)
Clinopodium vimineum, popular in Costa Rica as menta de palo, is an aromatic shrub native to Central America and the Caribbean. It is employed in traditional medicine to relieve gastrointestinal symptoms (carminative and antispasmodic properties). Thus, it is reported as an antimicrobial, sedative, analgesic, anti-inflammatory, healing, and antioxidant. Therefore, the nephroprotective effect of an aqueous extract of this plant was tested using a model of renal damage induced through potassium chromate in female Wistar rats. The plant material extract was prepared, and a test was carried out with four groups of five experimental subjects each. In addition to the control groups (positive and negative), one group was treated with the extract. Another was also given a pretreatment with this material prior to the induction of acute kidney injury. Each animal's renal function parameters were evaluated. They include creatinine, sodium, potassium, and glucose concentrations in serum and creatinine, sodium, potassium, glucose, and protein concentrations in urine. Urinary flow was obtained too. Furthermore, histopathological analysis of the kidneys was performed. The information obtained concluded that the aqueous extract of C. vimineum does not have a nephroprotective effect in the model of kidney damage induced with potassium chromate in female Wistar rats at the dose tested.